The role of Ivan Ohiienko in establishing Ukrainian identity through the prism of Ukrainian-russian war - Литвинюк, Оксана; Никитюк, Світлана (Іван Огієнко і сучасна наука та освіта, 2024)
The article investigate how Ivan Ohiienko’s life and heritage can be interpreted as a foundational reference for the current struggle for sovereignty and cultural integrity. Ohienko, a prominent linguist, theologian, and politician, emphasized the crucial role of language and culture in shaping Ukrainian identity. His advocacy for the Ukrainian language and the establishment of the Ukrainian Autocephalous Orthodox Church laid the groundwork for a distinct national consciousness, fostering a sense of unity and resilience among Ukrainians. In the context of the current confl ict, Ohiienko’s vision resonates deeply as Ukrainians confront external aggression. The war has ignited a renewed sense of patriotism and cultural pride, with many citizens actively promoting the use of the Ukrainian language in daily life, education, and media. This linguistic revival is not just a matter of communication but a powerful symbol of resistance against cultural assimilation. Moreover, the war has reinforced the importance of religion in the formation of national identity. Ohiienko’s emphasis on spirituality and community aligns with the role of the Ukrainian Orthodox Church in providing moral support and solidarity during these challenging times. As the nation grapples with the effects of war, Ohiienko’s legacy serves as a guiding light, inspiring Ukrainians to rally around their shared language, culture, and faith, ultimately fostering a strong sense of national identity amidst adversity.